Molecular characterization of scom_beromorus maculates (Ikan Tenggiri), atule Mate (Ikan Selar), and decapterus russelli (Ikan Selayang) species of fish from Malaysia marine ecosystem using dna sequence of mitochondrial dna (mtdna) cytochrome oxidase subunit I (COI) (DNA barcoding) - Ismail, Che Alhafizol Che (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
This study was undertaken to design a set of common primer to amplify the cytochrome oxidase I (COl) barcoding region of marine fish species. The primer set namely ST Fl 5'CACAAAGACATCGGCACCC3' (forward) and ST F3 S'AAGAATCAA/GAATAG/AGTGTTG3' (reverse) were able to amplify the three fish species namely Scomberomorus macu/ates (ikan Tenggiri), Atule mate (ikan Selar), and Decapterus russelli (ikan Selayang) chosen for this study. The sequence data generated were compared and analyzed using the sequence of COl gene of Gobio gobio (AB 239596) as a reference. On analysis between the three species Scomberomorus maculates and Atule mate have the highest percentage of similarities (76.91%), followed by Atule mate and Decapterus russelli (69.29%), and Scomberomorus maculates and Decapterus russe/li (64.45%) (Table 5). The sequence data generated were used to study their phylogenetic relationship by constructing a rooted neighbor joining (NJ) dendrogram (Fig. 18).